Negotiating taboo, gender, and shame in reyben entertainment's comment section - Brian Ramadhan Sono; Adya Zahira Nur Naomi; Surya Adi Wibowo; Dhea Chrisnatalia Sinambela; Tilka Asyarotun Kaamilah; Muizzu Nurhadi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study investigates how Indonesian digital audiences decode taboo narratives of female sexual agency and familial transgression through the comment section of the YouTube channel Reyben Entertainment, using Stuart Hall's (1980) Encoding/Decoding Model as an analytical approach and gender studies as the primary theoretical lens. Rather than treating the video text itself as the object of analysis, the study centers audience interpretation, examining how viewers negotiate the tension between a guest's framed sexual autonomy and the patriarchal norms that continue to police women's bodies and choices in Indonesian public discourse. Drawing on gender studies concepts such as the male gaze (Mulvey, 1975), Kodrat (the culturally inscribed expectation of proper womanhood), and Aib (shame as a disciplinary mechanism), the research reads comment discourse as a site where gender norms are reproduced, contested, and renegotiated rather than merely stated or accepted. Employing Creswell's (2014) six-step qualitative analysis process, forty-five audience comments were coded and organized to trace patterns of dominant-hegemonic, negotiated, and oppositional decoding. Findings show a fragmented reception landscape shaped primarily by gendered moral expectation: an oppositional majority condemns the guest's conduct as a violation of prescribed womanhood and family honor, alongside a critically literate segment that exposes the video's commercial fabrication; a negotiated cluster reframes her narrative through domestic duty and propriety rather than outright condemnation; while a dominant-hegemonic minority consumes the content voyeuristically, reproducing the very objectifying gaze the video's moral framing claims to critique. The study argues that these comment sections function as active sites of gendered ideological negotiation, where audiences continuously reassert, soften, or resist patriarchal expectations of women rather than passively receiving media messages. This research extends existing literature by shifting focus from production-side analysis and formal media texts to grassroots, gendered audience reception within unregulated, algorithmically evasive digital spaces.